prove this please it's urgent
Attachments:
![](https://hi-static.z-dn.net/files/d0f/e0601a7948acaff3c097802cacbb141b.jpg)
Answers
Answered by
1
Answer:
Here you go!
This is the proof
Attachments:
![](https://hi-static.z-dn.net/files/dd1/07edf6ed51113196ce35c38345456c6e.jpg)
Answered by
1
Answer:
Step-by-step explanation:
Let z = |x + iy|
| z | = √(x² + y²)
L.H.S:
|x - iy| / |-x + iy|
= | x + i (-y) | / | -x + iy|
= √ {x² + (-y)²} / √[(-x)² + y²]
= √(x² + y²) / √(x² +y²)
= 1
= R.H.S
Hence proved.
Similar questions